Depth profiling of surface damage in n-type GaN induced by inductively coupled plasma reactive ion etching using photo-electrochemical techniques. (24th September 2020) - Yamada, Shinji; Takeda, Kentaro; Toguchi, Masachika; Sakurai, Hideki; Nakamura, Toshiyuki; Suda, Jun; Kachi, Tetsu; Sato, Taketomo
Abstract: Depth profiling of the dry-etching damage in n-type GaN induced by inductively coupled plasma reactive ion etching was carried out by cyclical electrochemical impedance spectroscopy (EIS) measurements and damage-free photo-electrochemical (PEC) etching. The GaN samples were dry-etched under different etching bias power ( P bias ) conditions, and PEC etchings were conducted in increments of 10 nm after EIS measurements. The damage depth was determined to be less than 50 nm for the sample corresponding to P bias  = 30 W and was less than 10 nm for the two-step etching sample corresponding to P bias  = 30 W + 5 W.